STRESS AND FATIGUE LEVELS INDUCED BY STUDYING FOR THREE CONSECUTIVE SEMESTERS AMONG MEDICAL STUDENTS IN SAUDI ARABIA - Ebtehaj Saud Almughais, Rana Aboras , Mibashir Zafar , Abeer Mohammed Alshammari , Hialah Abdalluh Alenazi , Khaled Falah Alqhtani , Mazen Almansour; Shatha Hamza Alreheili , Fatmah Fahad Alreshidi , Atheer Yaser Alhazmi.Amal D Alshammari,Salma D Alshammari, Reem D Alshammari, Abeer Hassan Elhaj (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Background: The rigorous nature of medical education and the extended academic schedule can exert significant psychological and physical demands on students. The aim of this study to investigate the stress and fatigue levels experienced by medical students in Saudi Arabia that enrolled in three consecutive semesters implemented by the Ministry of Education. Method: A cross-sectional survey was conducted among different medical faculties across Saudi Arabia. Data were collected using an online questionnaire and included items of respondents’ stress ,fatigue levels, mental well-being, academic achievements, and perceptions of the quality of their educational experience. Data were analyzed using SPSS25. Results: The study participants (n=373) had a mean age of 22.23±1.86 years, with 60.3% being female students. 96.8%, were Saudi nationals. 11.3% reported smoking and (82.8%) lived with their families. Additionally, 28.2% of the students in fifth academic year. It was observed that exposure to three consecutive semesters explained approximately 42% (R2=0.42) of the variability in stress and fatigue levels among the study participants. In the three-semester system, 70% of students experienced concentration issues due to stress, work-life balance was unhealthy for many (44.5% somewhat, 18.2% significantly), physical health was affected for most (74.3%), and mental health compared to a two-semester system was slightly worse (35.4%) or much worse (20.4%). Overall, as about the same (38.3%), reported the apparent quality of learning (38.3%), (24.9%) somewhat lower, or (18.8%) much lower, with few indicating any improvements. Conclusion: Our study highlights the notable stress and fatigue experienced by medical students through three consecutive semesters.